THE ROLE OF CONSUMERS IN THE CIRCULAR ECONOMY: A LITERATURE REVIEW ON CONSUMER PROTECTION REGULATIONS AND SUSTAINABILITY - Naufal Shofwan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
In facing global sustainability challenges, consumers play a strategic role in shaping the direction of the circular economy. This article presents a literature review on the relationship between consumer protection and the transition toward a sustainable consumption model. The main focus is directed at three key issues: the right to environmental information, the right to repair, and regulatory challenges related to greenwashing practices. By using a narrative literature review approach, this article examines various academic and policy sources to evaluate the extent to which consumer protection has been integrated into circular economy strategies. The findings show that although positive initiatives have been taken, regulatory implementation remains weak and often fails to provide effective protection mechanisms for consumers. The policy implications proposed include strengthening standards for environmental claims, expanding the right to repair across sectors, and increasing sustainability literacy at the consumer level. This article aims to enrich academic discourse and serve as a foundation for consumer-based policy development in support of the circular economy agenda.